2021
DOI: 10.1017/jfm.2020.916
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and entropy indirect noise generated in subsonic non-isentropic nozzles

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…( 26)). In keeping with the earlier current results and previous investigations [20,33,57], this figure shows that the entropic wave is more strongly annihilated at higher frequencies. It also reveals that the compositional sources are highly affected by the flow thermo-hydrodynamics at high frequencies.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…( 26)). In keeping with the earlier current results and previous investigations [20,33,57], this figure shows that the entropic wave is more strongly annihilated at higher frequencies. It also reveals that the compositional sources are highly affected by the flow thermo-hydrodynamics at high frequencies.…”
supporting
confidence: 92%
“…These traces show that, as expected, during the advection process, the wave amplitude decreases, while the width increases. This is evidence for the wave dissipation and deformation, resulted from turbulence mixing and diffusion [35,53]. The strongest elongation of the waves is observed in the first half of the channel, while the amplitude decrement gradually continues until the outlet.…”
Section: Wall Conditionsmentioning
confidence: 86%
See 2 more Smart Citations
“…However, many practical applications require solutions for non-isentropic mean flows. For instance, De Domenico et al (2021) and Yang, Guzmán-Iñigo & Morgans (2020) recently showed that, in the diverging portion of realistic nozzles, the flow can separate creating recirculation regions and, hence, turbulence both leading to mean flow non-isentropicity and strong deviations from isentropic acoustic theories. Another source of non-isentropicity can be heat transfer, as happens in combustors and heat exchangers.…”
Section: Introductionmentioning
confidence: 99%